Nature Walks Peripatetic Tradition in the Non-fiction Travel Writing of Robert Macfarlane - Wilczynski, Marek; Wilczynski, Marek; Dziok, Anna (Peter Lang, 2023)
This book, Nature Walks: Peripatetic Tradition in Non-fiction Travel Writing of Robert Macfarlane examines pedestrianism in the long history of British travel writing and examines the consequences that foot mobility has for the walking self and for the meaning-making of the surrounding world. This book also discovers how the books by Robert Macfarlane, a widely read British author, on the one hand, uphold some of the long-established tenets of the travel genre, and, on the other hand, demonstrate an openness to departure, renewal, and the reconfiguration of discursive practices. Nature Walks offers a profound examination of the ways by which literary language may respond to our present environmental challenges.